Good Governance dalam Program Beasiswa Karawang Cerdas Kabupaten Karawang - Muhamad Mahrus Zamzami; Dadan Kurniansyah; Rachmat Ramdani (Peneliti.net, 2022)
This study discusses Good Governance in the Karawang Cerdas scholarship program conducted by the Karawang Regency Government. This study uses a qualitative descriptive method with data taken through interview techniques, observation and documentation studies. After that, the data were analyzed through three stages of reduction, presentation and drawing of initial and final conclusions. The purpose of this research in general is to find out and analyze whether the implementation of the Karawang Cerdas scholarship program has been running optimally in accordance with the principles of good governance. The results of this study indicate that the actualization of the Karawang Smart scholarship program is still not optimal, where there are technical errors, lack of transparency and incomplete information in addition to the emergence of new problems in Karawang that hinder the allocation of Karawang Cerdas. However, as a rule, the Karawang cerdas Scholarship is considered to have met the eligibility standards because the regulations have been made well in the Karawang Regent Regulation Number 66 of 2018 concerning the Karawang Cerdas Program.